An AMR Parser For English, French, German, Spanish and Japanese and A New AMR-Annotated Corpus - Vanderwende, Lucy; Menezes, Arul; Quirk, Chris (Proceedings of the 2015 Conference of the North American Chapter of the Association for Computational Linguistics: Human Language Technologies(NAACL HLT), 2015, 2015)
In this demonstration, we will present our online parser that allows users to submit any sentence and obtain an analysis following the specification of AMR (Banarescu et al., 2014) to a large extent. This AMR analysis is generated by a small set of rules that convert a native Logical Form analysis provided by a pre-existing parser (see Vanderwende, 2015) into the AMR format. While we demonstrate the performance of our AMR parser on data sets annotated by the LDC, we will focus attention in the demo on the following two areas: 1) we will make available AMR annotations for the data sets that were used to develop our parser, to serve as a supplement to the LDC data sets, and 2) we will demonstrate AMR parsers for German, French, Spanish and Japanese that make use of the same small set of LF-to-AMR conversion rules.